The Red Moon and Beyond: Astronomical Events in the Context of Global Faith and Culture - Belay Sitotaw Goshu; Muhammad Ridwan (Britain International for Academic Research (BIAR-Publisher), 2024)
This study uses a linear regression model to predict lunar eclipses (red moons) from 2025 to 2050 by integrating scientific, religious, and cultural viewpoints. According to science, the reddish-hued moon during a lunar eclipse is caused by Rayleigh scattering, which happens when Earth's atmosphere blocks off shorter wavelengths. Red moons are associated with eschatological signals in many religious traditions, such as Christianity and Islam. However, in some civilizations, such as Ethiopian, Egyptian, and Jewish, the red moon has important spiritual and cultural significance. The forecasting model employs Ordinary Least Squares (OLS) regression based on past lunar eclipse data. With an R-squared value of 0.999 and an adjusted R-squared of 0.999, the model produced a precise fit that showed almost perfect agreement between the observed and anticipated eclipse timings. The significance of the model is validated by the F-statistic of 24,800 and the p-value of 1.49e-41. With a t-value of 157.48 and a p-value of 0.000, the slope coefficient of 359.9 days per year closely matches the established lunar cycle, demonstrating the cycle's statistical significance. The Durbin-Watson statistic (1.704), one of the diagnostic tests, shows no evidence of considerable autocorrelation. Culturally speaking, lunar eclipses have been interpreted as prophecies or occasions for rites in countries like Ethiopia and Egypt and among Arab and Jewish populations. The model's predictive power for eclipses in the future provides important information for scientific and cultural purposes.